2022
DOI: 10.1155/2022/9333328
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Quality Control of Medical Equipment Based on Information Fusion Technology

Abstract: In the medical field, to ensure the use of large medical equipment, it is necessary to carry out regular maintenance on large medical equipment. In the process of maintenance and maintenance of large-scale medical equipment, most medical personnel have not established a corresponding quality management system, neglecting daily maintenance and maintenance, resulting in many hidden dangers of medical accidents. To this end, the quality control of large medical devices should be strengthened, the control before, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These findings align with existing research, which consistently identifies limited technological knowledge, skills, and a lack of education and training as significant barriers to the implementation and acceptance of telemedicine interventions [ 22 , 23 ]. Furthermore, effective planning for equipment maintenance is paramount to ensure the efficient and effective provision of telespecialty care [ 24 ]. Previous research investigating the challenges of maintaining eye care equipment revealed that equipment breakdowns led to frustrating delays in conducting proper examinations and increased the risk of disease progression, resulting in poorer treatment outcomes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with existing research, which consistently identifies limited technological knowledge, skills, and a lack of education and training as significant barriers to the implementation and acceptance of telemedicine interventions [ 22 , 23 ]. Furthermore, effective planning for equipment maintenance is paramount to ensure the efficient and effective provision of telespecialty care [ 24 ]. Previous research investigating the challenges of maintaining eye care equipment revealed that equipment breakdowns led to frustrating delays in conducting proper examinations and increased the risk of disease progression, resulting in poorer treatment outcomes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between January 2019 and December 2020, a study was conducted involving 643 ‘LINAC down’ events, with equipment manufacturers also included as participants [ [14] , [15] , [16] ]. The inclusion criteria included the following: 1) LINAC faults, 2) the involvement of eight LINACs from three manufacturers, and 3) the application of varied improvement measures for different faults.…”
Section: Information and Methodologymentioning
confidence: 99%
“…A medical device registry is a structured system with the primary objective of enhancing awareness of the role that medical devices play in elevating the quality of patient care consistently [27]. It systematically collects relevant data, evaluates significant outcomes, and comprehensively addresses the population's exposure to specific medical devices on a broad scale, ranging from global to national, regional, and healthcare system levels [28].…”
Section: Medical Device Registriesmentioning
confidence: 99%